Tired of email? Examining the role of extraversion in building energy resources after dealing with work-email. Issue 3 (4th May 2022) - Russell, Emma; Woods, Stephen A.; Banks, Adrian P.
ABSTRACT: Office-based work today involves dealing with email, despite being denigrated and lauded in almost equal measures. Using the Conservation of Resources theory we examine whether Extraversion (expressed through two facets) acts as a resource to explain the differential impact that work-email has on people's energy resources (relating to fatigue and boredom). An experience-sampling study was undertaken, whereby 54 knowledge-workers completed records of their response (n = 589) to new work-email over the course of a typical working day. Results were analysed using hierarchical linear modelling (HLM). Participants who felt tired prior to dealing with email, reported that they felt more energized afterwards (but only if they were higher on Agentic extraversion). Work-email did not re-energize extraverts when they had been bored beforehand. By examining changes in energy resources, and by measuring different facets of Extraversion, we offer theoretical and methodological contributions to advancing understanding about the role of resources in dealing with work-email. Specifically, our results suggest that Extraversion may not constitutionally be a key resource within COR, because its value and contribution to resource building is contingent on context. Implications for practitioners concerned with how best to manage digital communications at work, are discussed.